Current therapeutic options for Huntington's disease: Good clinical practice versus evidence-based approaches? - Killoran, Annie; Biglan, Kevin M. (Movement disorders, 2014)
ABSTRACT Therapeutic decision‐making in Huntington's disease (HD) is often guided by clinical experience, because of the limited empirical evidence available. The only medication for HD that has met the regulatory hurdle for approval is tetrabenazine, indicated for the treatment of chorea. However, its use has limitations, and in the setting of specific contraindications or comorbidities the treatment of choice for chorea is still the multipurpose antipsychotics. For the management of psychiatric disturbances, selective serotonin reuptake inhibitors (SSRIs) and mood stabilizers are often used, although empirical evidence is lacking. Finally, no known effective treatment is available for cognitive dysfunction in HD. We discuss the limited evidence available and current expert opinion on medical treatment of the dominant motor, psychiatric, and cognitive features of HD. This follows a brief introduction on the general principles of HD management and on evidence‐based medicine in relation to clinical practice. © 2014 International Parkinson and Movement Disorder Society